PENENTUAN KOMPOSISI CRUDE OIL PADA PROSES BLENDING DENGAN PENDEKATAN ALGORITMA GENETIKA - Miftahol Arifin; Grahan Rizka Pradita (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2021)
PT PERTAMINA (Persero) Refinery Unit IV is a natural distilation oil company. The process of blending crude oil done in PT PERTAMINA (Persero) Refinery Unit IV often produces feed imperfectly. The product’s fraction produced from this blending process can not get maximum output. What is needed is optimazing the determination of crude oil composition during the process of blending crude. The aim of this process is to separate the contain of LPG, Light Naphtha, Heavy Naphtha, kero, Light Gas Oil (LGO), Heavy Gas Oil (HGO), LSWR (Low Sulfur Wax Residue) with other composition in order to suit with colom capacity in Crude Destilation Unit II (CDU II). The aim of this research is determining the composition of crude oil from every oil tank to be feed in CDU II. With optimal percentage, the expectation is to increase the number of product fraction from blending process. The solving of this problem is using simplex method the approach of genetic algorithm. The advantage of genetic algorithm in the development of chromosome, it can be done randomly based on the number of determined popsize. Besides, the alternative of chromosome will have bigger probability than using the simplex method. The result of calculation using the genetic algorithm method produces the total precentage of crude oil’s composition 99,91% and the composition of volume feed 229.774 MB. With composition volume feed for CDU II 41.285 MB pulled back from oil tank 71T-4, 55.384 MB from oil tank 71T-12, 71.852 MB from oil tank 71T-16 and the last 61.249 MB from oil tank 71T-105. The estimation of result not be different away by the solution produced simplex method.